Benchmarking Brain-Training Apps Using DEGREE and Fuzzy Logic: Lumosity vs Elevate - Sismoro, Heri; Kurniawan, Mei Parwanto (Informatika, Universitas Jenderal Soedirman, 2026)
This study provides an actionable benchmark of two popular brain-training apps—Lumosity and Elevate—by applying the 14-factor DEGREE framework as a structured UX evaluation tool and using fuzzy scoring to improve interpretability. We recruited 190 Computer Science undergraduates; each participant evaluated both apps, yielding 380 app evaluations using a counterbalanced two-sheet questionnaire. Fourteen factors covering usability, engagement, and perceived learning were rated on a five-point Likert scale. Reliability was strong for both apps (Cronbach’s α = 0.822 for Lumosity; 0.847 for Elevate). Descriptive results showed mid-to-high perceptions overall, with mean scores of 3.51 (Lumosity) and 3.44 (Elevate). Fuzzy aggregation transformed subjective ratings into a 0–1 index, producing overall scores of 0.503 (Lumosity) and 0.490 (Elevate), indicating a small global advantage for Lumosity. At the factor level, Lumosity was slightly higher on most DEGREE dimensions, whereas Elevate showed relative advantages on Learnability and Confidence, suggesting potential benefits for early onboarding and self-efficacy. Overall, the proposed DEGREE–Fuzzy pipeline yields a transparent, reproducible benchmark that translates multi-factor perceptions into decision-ready recommendations for selecting apps aligned with instructional goals.